Remittances and household welfare: Findings from the Myanmar Household Welfare Survey (MHWS) - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2023)
Remittances are a critical source of household income in Myanmar and are significantly associated with positive welfare outcomes. In 2022, 33 percent of the households surveyed in the Myanmar Household Welfare Survey (MHWS) received remittances at least once in the twelve-month period. Remittances made up 7 percent of the average monthly per capita income of households in 2022. Among households that received remittances, 40 percent of their average monthly per capita income was from remittances. Considerably more households received remittances in 2022, compared to 2017, the last year for which there is nationally representative data (World Bank 2017). Despite the increase in the number of households receiving remittances, compared to 2017, the income share from remittances has decreased for all households. Even with internal lockdowns and border closures because of the COVID-19 pandemic, remittance senders migrated internally in 2020 and 2021. As a result, domestic remittance flows appear to have increased steadily since 2012. International remittance flows, on the other hand, decreased substantially during the first two years of the pandemic. They are now increasing rapidly. In 2022, households in Rakhine, Chin, Mon, and Kayin received the most remittances of the states/regions. Households in Chin, Kayin, Tanintharyi, and Mon received a greater percentage of remittances from international senders rather than domestic senders. Most international remittance flows were from Thailand, Malaysia, and China. Households in Kachin, Ayeyarwady, and Mandalay received the most remittances from domestic senders. Most domestic remittance flows were from Yangon, Mandalay, and Shan. Receiving remittances has a positive and significant association with improved welfare outcomes. Households that receive remittances are less likely to have lower income compared with last year and more likely to have a better food consumption score and a higher dietary diversity score. Households who receive remittances use fewer coping strategies. Finally, households who receive remittances are more likely to have an improved house made of brick, brick/wood, or semi-pucca.